PENTOXIFYLLINE IN ACUTE ISCHEMIC STROKE PATIENTS WITH BLOOD HYPERVISCOSITY - Rasyid, Al; Harris, Salim; Nurhayat, Eny; Prihartono, Joedo (International Journal of Applied Pharmaceutics, 2018)
Objective: This study evaluated the efficacy of pentoxifylline, a hemorrheologic agent, for treating acute ischemic stroke in patients with blood hyperviscosity. Methods: Patients were randomly allocated within 3 days of stroke onset to study or control treatment. All the patients received the standard acute ischemic stroke treatment. The study treatment was intravenous pentoxifylline 1200 mg/day for 5 consecutive days and oral pentoxifylline 800 mg in two divided doses for 23 days. Blood viscosity was evaluated on days 7 and 30. The outcomes were assessed by the National Institutes of Health Stroke Scale (NIHSS), modified Rankin Scale, and Barthel index (BI) criteria. Results: The median baseline viscosity was 6.89 poise in the study and 6.46 poise in the control groups and had decreased in all the patients on days 7 and 30. The decrease in the study group on day 7 (1.13 poise) was greater than that in the control group (0.57 poise); the difference was not significant. The NIHSS score improved by 32% in the study group (relative risk [RR]=1.00, 95% confidence interval [CI]: 0.421–3.556; p=1.00). At 1-month, 67% of the study group had a good functional outcome (RR=1.026, 95% CI: 0.656–1.605; p=0.909). Conclusion: Pentoxifylline decreased blood viscosity and improved clinical outcome in this patient series.